Dinamika kapitalisme dan dampaknya terhadap kesenjangan sosial: Sebuah kajian literatur - Wafa, Muhammad Ali (Maliki Interdisciplinary Journal, 2024)
Capitalism is an economic system that emphasizes private ownership of the means of production and economic freedom without state intervention. Capitalism, especially in developed countries, has driven economic growth and innovation since its emergence in the 16th century. However, this system also has a detrimental effect, namely large social imbalances, which cause wealth to be distributed unevenly and focused on the bourgeoisie. In capitalist societies, social hierarchies often lead to injustice and discrimination, and materialism promotes solidarity. This study emphasizes the impact of capitalism on social welfare and wealth distribution. It also reviews the perspectives of figures such as Pierre Bourdieu, Ayn Rand, Adam Smith, Max Weber, and Karl Marx on capitalism. This study is expected to improve our understanding of capitalism.